A critical review of field relationships and gravitational origin of active normal faults in the Kashmir basin, NW Himalaya. Issue 4 (1st December 2020) - Ahmad, Shah Afroz; Sahari, Syaakiirroh; Qadir, Asiya; Manan, Nurhafizah Abd
Abstract: Kashmir basin is a piggyback basin that has developed at the last stage of the ongoing collision between India and Eurasia, and it is ~4 Ma old and contains 1300 m thick blanket of Plio-Pleistocene to Holocene deposits. These unconsolidated sediments are locally known as Karewas, which are deformed and displaced by a number of normal faults. These young normal faults are previously linked to the tectonic collision, however, here we question such consensus on the tectonic origin of the faults by demonstrating that the widely reported field evidence for active normal faulting in Kashmir is actually non-tectonic because the faults have formed by gravitational tectonics. This was achieved by reevaluation of all of the major studies that have reported the field data on active normal faulting in the region. We supplement our results with the structural, geological, geodetic and earthquakes centroid moment tensor data, which clearly consolidate our interpretations and demonstrate that active normal faults in Kashmir basin are not tectonically formed, and instead the lithological contrast between the Upper and Lower Karewas have created suitable conditions for structural failure. So, the faults are active, and would be expected to remain so as long as the vertical load favors the slip on the faults but these faults will not produce major earthquakes as are expected on the major Himalayan fault systems, and therefore the seismic hazard associated with such faults is minimum, which needs to be quantified and implemented in the future earthquake scenario maps.